The Impact of Socio-Personal Profile on Organisational Climate Perception: An Empirical Study - Kumar, Suresh (Prabandhan: Indian Journal of Management, 2012)
Organizational Climate is the summary perception which people have about an organization. It is a global expression of what the organization is. The present investigation is an attempt to understand the organizational climate concept and to explore the influence of socio - personal variables on the building of organizational climate perception. The study was conducted on 360 respondents belonging to Bhakra - Beas Management Board (BBMB), an enterprise in India. The study was conducted during 2008 to 2010. It was generally perceived that the organizational climate is perceived equally by the all employees. Is there any significant mean difference on organizational climate score according the socio personal variable groups? The present study findings suggest that the majority of organizational climate dimensions were found to be significantly differed and the employees expectations were found to have been fulfilled in all formats. Finally, the gender, background, occupational status and the time to fulfill spiritual needs variables support the alternate hypothesis. After a detailed discussion, it was found that most of the employees have perceived organizational climate as moderate. The mean difference on organizational climate perceptions also shows significant results. Thus, the perception groups were found to be significantly ranged.